2022
DOI: 10.1097/gox.0000000000004387
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Somatic Consequences of Digital Amputation

Abstract: Background: Major limb amputation is a devastating potential outcome of trauma, tumor, or disease. Much has been written about the physical, functional, economic, and psychological consequences of major limb loss. In contradistinction, considerably less has been written concerning the consequences of “minor” limb loss, specifically single partial digit amputations. Are minor limb (partial single digit) amputations associated with symptoms of psychological disorder similar to those reported for major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Psychologically and socially, hand/arm amputations can be more debilitating and limiting than any other disability, not to mention inconvenient in everyday life. 9 24 25 26 27 28 29 30 31 32 However, hand/arm transplantation has drawn little medical interest as there is an alternative (prosthetic limbs) and the procedure has often been underestimated or ignored, especially in the field of transplantation, since the hand is not a vital organ. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Psychologically and socially, hand/arm amputations can be more debilitating and limiting than any other disability, not to mention inconvenient in everyday life. 9 24 25 26 27 28 29 30 31 32 However, hand/arm transplantation has drawn little medical interest as there is an alternative (prosthetic limbs) and the procedure has often been underestimated or ignored, especially in the field of transplantation, since the hand is not a vital organ. 29 …”
Section: Discussionmentioning
confidence: 99%
“…By Skoff H, Skoff H. Plast Reconstr Surg Glob Open 2022;10:e4387. 9 This cohort study investigates the long-term psychologic outcomes associated with single-digit amputation. Twenty-five patients without psychiatric history answered three validated questionnaires to determine somatic and psychologic outcomes after digital amputation.…”
Section: University Of Washingtonmentioning
confidence: 99%
“…In addition to the functional losses of the hand following finger amputation, patients often deal with ongoing psychological effects. One study examining the role of finger amputation reported that 96% ( n = 25) of affected patients reported symptoms such as anxiety, depression, or post-traumatic stress disorder (PTSD) in the 3 months following their amputation [ 11 ]. Such psychological effects can decrease the quality of life for patients.…”
Section: Introductionmentioning
confidence: 99%